Influence of Neonatal Factors on the Eruption of Primary Teeth in Children - Devraj, Indira M.; Nandlal, Bhojraj; Narayanappa, Doddaiah; Deshmukh, Seema; Dhull, Kanika S. (Medicine and Medical Research: New Perspectives Vol. 5, 2024)
Introduction: The relation between neonatal factors and the timing of eruption of primary teeth has not been studied prospectively among Indian preterm infants. The eruption of the first primary teeth is a normal physiological process. The eruption of primary teeth is significantly influenced by prenatal and neonatal variables as well as dietary deficiencies throughout pregnancy. The eruption of primary teeth is predominantly influenced by neonatal variables, including birth weight, intensity of neonatal sickness, gestational age (GA), and degree of prematurity. Aims: The present study evaluates the influence of neonatal factors on the eruption of primary teeth in children born preterm. Materials and Methods: A prospective longitudinal cohort study design was adopted. A total of 150 subjects were recruited by simple random sampling. Each child was followed up from birth up to 36 months. An intraoral examination was done and the teeth present in each visit were recorded. Data were statistically analyzed and interpreted. Descriptive statistics, t-tests for independent samples, and Pearson’s chi-squared tests were applied. Tooth showing a statistically significant difference in mean age of eruption between term and preterm categories was studied for the effect of maternal and neonatal characteristics on eruption using multivariate regression analysis. Results: The mandibular central incisor was the first tooth to erupt. A significant determinant of the eruption of mandibular incisor in term children was found to be parity, weight for GA, and complementary feeding, whereas, for preterm children, significant determinants were parity, birth weight birth length, weight for GA, and complementary feeding. Children born second had delay in the eruption of all primary teeth compared to the first child in both the groups. This effect was statistically significant for mandibular incisors in both term and preterm groups and statistically insignificant for all the other teeth suggesting that parity affects only the eruption of first primary teeth. Conclusion: Neonatal factors, such as birth weight, birth length, weight for GA, and introduction of complementary feeding have a strong significant association with the eruption of primary teeth. The findings of this study will guide the preventive management of oral health in preterm children. Clinical Significance: The findings of this study will guide the preventive management of oral health in preterm children.